Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3892/ijo.2012.1372
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic membrane-derived epithelial stem cells display anticancer activity in BALB/c female nude mice bearing disseminated breast cancer xenografts

Abstract: Abstract. Breast cancer is one of the most common malignant tumors and the leading cause of mortality among women. In this study, we propose a human stem cell transplantation strategy, an important method for treating various cancers, as a potential breast cancer therapy. To this end, we used human amniotic membrane-derived epithelial stem cells (hAECs) as a cell source for performing human stem cell transplantation. hAECs have multipotent differentiation abilities and possess high proliferative potential. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In this study, results from a cytokine array revealed that hAECs released various cytokines which are able to induce G0/G1 cell cycle arrest, including TGF-β1 ( 22 ), GM-CSF ( 23 ), IL-8 ( 24 ), IL-6 ( 25 ), IL-1 ( 26 ), IFN-γ, TNF-α ( 27 ), TGF-β2 ( 28 ) and Smad 7 ( 29 ). Our results showed that the secretion of TGF-β1 derived from hAECs was abundant, this is consistent with the report of Kang et al showing the amount of TGF-β1 ranked first among those anticancer-associated factors ( 9 ). We used recombinant human TGF-β1 to imitate the function of hAEC-secreted TGF-β1 on EOC cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, results from a cytokine array revealed that hAECs released various cytokines which are able to induce G0/G1 cell cycle arrest, including TGF-β1 ( 22 ), GM-CSF ( 23 ), IL-8 ( 24 ), IL-6 ( 25 ), IL-1 ( 26 ), IFN-γ, TNF-α ( 27 ), TGF-β2 ( 28 ) and Smad 7 ( 29 ). Our results showed that the secretion of TGF-β1 derived from hAECs was abundant, this is consistent with the report of Kang et al showing the amount of TGF-β1 ranked first among those anticancer-associated factors ( 9 ). We used recombinant human TGF-β1 to imitate the function of hAEC-secreted TGF-β1 on EOC cells.…”
Section: Discussionsupporting
confidence: 93%
“…Niknejad et al reported that hAEC-conditioned medium (hAEC-CM) could induce apoptosis in HeLa cells and MDA-MB-231 cells in vitro ( 8 ). Kang et al showed that hAECs displayed anticancer activity in a breast cancer-bearing nude mouse model through both cell-to-cell contact and paracrine way ( 9 ). However, Mamede et al revealed adverse effects of amniotic membrane-extracted proteins on human cancer cell lines tested by MTT assay in vitro ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, the expression of telomerase hTERT in hAESCs is not detected, explaining why hAESCs do not generate tumors. Notably, several studies demonstrated that hAESCs could inhibit tumor cell growth and induce apoptosis of cancer cells, including HeLa cells and breast and ovarian cancer cells [ 94 , 95 , 96 ]. However, Yang et al reported that co-injection of hAESCs and Raji tumor cells into immunodeficient mice shows a similar survival duration when compared with the mice receiving only Raji cells, which indicated hAESCs have little effect on tumor growth [ 29 ].…”
Section: The Safety Evaluation Of Human Amniotic Epithelial Stem Cmentioning
confidence: 99%
“…We confirmed the ability of HB1.F3.CD, HB1.F3.CD.IFN-β, or HB1.F3.CE cells to migrate toward LNCaP prostate cancer cells. The tumor-tropic effects of stem cells are generally attributed to growth factors and cytokines [30,31]. Real time-PCR analysis demonstrated that the LNCaP prostate cancer cells expressed several cytokines including VEGF, MCP-1, and SCF.…”
Section: Discussionmentioning
confidence: 99%